Development of a national, standardized simulation case template. Issue 6 (November 2020) - Baylis, Jared; Heyd, Christopher; Thoma, Brent; Hall, Andrew K.; Chaplin, Timothy; Petrosoniak, Andrew; McColl, Tamara; O'Brien, Michael; Deshaies, Jean-François; Caners, Kyla
ABSTRACT: Emergency medicine (EM) training programs incorporate simulation for teaching as well as formative and summative assessment. The development of a simulation curriculum for Canadian postgraduate EM programs is underway and would be facilitated by a standardized, user-friendly, nationally endorsed simulation template. We convened a nationally representative group of simulation educators to participate in a three-phase process to develop and refine a simulation case template for Canadian EM educators. Participants provided feedback by means of free text comments and focus groups which were analyzed to inform modification of the template. We anticipate that this template will facilitate the sharing of cases across sites and the development of standardized cases for simulation-based assessment.